ASURANSI KESEHATAN BERDASARKAN UNDANG-UNDANG NOMOR 3 TAHUN 1992 - Suryono, Arief (Jurnal Dinamika Hukum, 2009)
Health insurance according to the Law No. 3/1992 obout the social employment guarantee which consist of responsiver and the addressee and health service provider is the health social insurance which is aimed to give the health care guarantee toward the addressee that is enterprenaur and worker.  The law relationship which is consisted between: Responssiver-Addressee is the insurance relationship; Responssiver-Health services provider is the user of health service belong to the health service provider toward to the addressee; Health services provider-Addressee is gives the health service to the addresse is patient.  The responsibility of the responssiver toward the addressee is to give the health care insurance to the addressee gives the health service provider for the importance of the addressee. Kata Kunci:  Asuransi Kesehatan